The Penggunnaan E-learning Melalui Aplikasi Cisco Webex Meeting Dalam Pengajaran Bahasa Inggris di SMAN 18 Makassar - Novianti Pabanne; Siti Haliah Batau; Nurfaizah Sahib (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
The objective of the research was to find out whether or not the use of E-Learning through Cisco Webex Meeting application enhance students’ writing skill at grade XII SMAN 18 Makassar. This research used an pre-experimental method. This research conducted in three steps such as pre-test, treatment, and post-test. The sample of this research is class IPA XII IPA 2 membered 27 students. Data colleting by using pre-test and post-test. After analyzing the data, the writer concluded that the use of the cisco webex meeting application in teaching English could enhance students’ writing of grade XII IPA 2 SMAN 18 Makassar it was proved with the mean score of the students in the pre-test was 52,96 and the post-test was 76,67. The calculated significance value is 0.000 less than 0.05 (P-value = 0.000 < 0.05). If the significance is less then 0,05 so, this research hypothesis is accepted. Thus the use of Cisco Webex application as a learning media can enhance students' writing skill at SMAN 18 Makassar.